Simultaneous EUS-FNA Diagnosis and TNM Staging of a Pancreatic Neuroendocrine Tumor in a Patient with an Unrecognized MEN Type 1. (10th October 2012) - Ferrara, Francesco; Luigiano, Carmelo; Maimone, Antonella; Bassi, Marco; Polifemo, Anna Maria; Baccarini, Paola; Cennamo, Vincenzo; Cremonini, Nadia; Fabbri, Carlo
Abstract : We report the case of a woman who, during oncological followup for bronchial carcinoid (diagnosed in 2005), papillary thyroid carcinoma, and bilateral parathyroid adenoma (simultaneously diagnosed in 2007), performed a pancreatic endoscopic ultrasonography with fine needle agobiopsy (EUS-FNA) for a positron emission tomography (PET) suspicion of pancreatic and hepatic lesions; during the procedure, the pancreatic and liver lesions were confirmed, and a peripancreatic lymph node involvement was found, allowing a complete pTNM staging during the same procedure.